Programa Saúde na Escola : limites e possibilidades intersetoriais - Silva Junior, Aristides José da (2014)
This study presents a proposal of approaching to health and education intersectoral actions adopted by public policies. These strategies are the option for developing health promotion directed to students of public schools, to take care of the vulnerabilities to which this population is exposed. We choose the School Health Program (Programa Saúde na Escola - PSE) as a relevant intersectoral action that brings together the areas of Education and Health, as their effectiveness to offer attention to the population. Through PSE, the aim of this research is: to promote a reflection on the limits and possibilities for intersectoral development of self care at school. With a qualitative approach, we used semi-structured interviews, as well as analysis of the resonant narratives. In a second movement, to approach to cross-sectoral dialogues, we take a narrative of our own experience in implementing this intersectoral action. The results underline the need of policies to direct attention to health problems at school, however intersectoral actions are still incipient. Dichotomies are found in the School Health Program, as it is prescribed by the health sector to be developed by the education sector, thereby occurring a sectoral view of an intersectoral program. The lack of coordinated and integrated among managers of various government actions, as well as professionals, result in several limits: the bureaucratization of services; the waste of time of financial and human resources and also duplicity of actions, which do not keep the pursue of the program objectives. School can be the setting where it is promoted self-care, but for this, various movements are still necessary: recovery and forming of health and education workers, infrastructure investments and improving access to health services. Actions such as these are essential to achieve the objectives of the intersectoral and thus promote health at school.